Examining the Mediating Effect of ICT Adoption on Personnel Training and Technological Infrastructure in Local Government Revenue Generation - AbdulKareem, Abdulrazaq Kayode; Akintola, Muslim Akinbola; Ameen, Abdullateef; Isiaka, Sulu Babaita; Omolabi, Isa; Amosa, Jimoh Rafiu (Journal of Technology Management and Business, 2025)
This study provides valuable insights into the dynamics of Information and Communication Technology (ICT) adoption concerning revenue generation within the Nigerian local government system. By analysing the mediating role of ICT adoption in relation to personnel training, technological infrastructure, and revenue collection, this study advances the understanding of how technology serves as a catalyst for converting human and technological resources into tangible organizational outcomes. This study investigates beyond surface-level interactions to reveal the complex interplay among these variables through a quantitative method of data collection and analysis. Data were collected through a structured questionnaire from the revenue staff of Ilorin West Local Government of Kwara State, Nigeria. The findings reveal that well-trained personnel and robust technological infrastructure synergistically contribute to the adoption of ICT, resulting in optimized revenue collection mechanisms. Thus, this study underscores the transformative potential of technology, positioning it as a cornerstone for organizational growth and efficiency. The findings provide a framework for comprehending the pathways through which technology permeates various dimensions of local government organizations, leading to enhanced revenue management and performance.